Strategic plan of AZ Agri Products Corporation - Valdez, Carol V.; Soledad, Miguel D.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2010)
The Philippine farming or crop production accounts for majority of the country?s gross national product generated by the Agriculture Industry. Despite its? declining productivity, the Agriculture still remains to be an important industry as it helps address the nation?s economic challenges and fast growing population. Fertilizers belong to agri-inputs or farm inputs sub-sector of the agriculture business. Agri-inputs enhance crop production by supplementing nutrient requirements of plants. The fertilizer business is therefore explored in this paper. However, records on the industry?s production and consumption is aggregated which limits available data?s true reflection of the whole fertilizer business. AZ Agri Products Corporation (AZAP) is an All-Filipino importer, distributor of AZ41 Organic Foliar Fertilizer. AZAP has a vision to be the premier environment-friendly agri-input provider in the Philippines and Asia-Pacific region. AZAP translates this vision into goals and lives by the company?s theme of ?THE FUTURE IS GREEN?. The company endeavors to continuously delight customers with effective environment and human-friendly products to maintain satisfied employees and to grow shareholders? profits. AZAP?s banner product, AZ41 Organic-based Foliar Fertilizer is slowly establishing a name for itself in crop production sub-sector. The product is named AZ41 to convey completeness (Macro and Micro-nutrients from Vitamin A to Z) and for its 4 key qualities ? foliar fertilizer (crop nutrition), sticker/spreader, fungicidal and insecticidal properties. The main ingredients are from renewable and sustainable resources thus making it safe, non-toxic, biodegradable and environmentally friendly. The product?s combined unique properties have elicited patronage from local farmers and generated interest from fertilizer and other chemical companies. Competition almost came up with new and almost-similar products to match AZ41?s fertilizer and pesticidal properties. In this strategic paper, the PEST tool and Michael Porter?s Five Forces Model are used for the analytical framework of the external environment. Competitive forces, socio-cultural, technological, ecological, economic and political factors were reviewed to determine the forces affecting the external environment of AZAP. Opportunities and threats were identified to help strengthen the company?s position in the industry. The different functional areas of the company such as General Management, Human Resources, Finance, Marketing and Operations were also assessed to determine the company?s internal strengths and weaknesses before strategies were conceptualized. Result from Internal and External Environment Analysis were used to develop strategic options. Internal-External (IE) Matrix and the Strenght-Weaknesses-Threat-Opportunities (SWOT) Matrix generated nine (9) alternative strategies. The use of Quantitative Strategic Planning Matrix (QSPM) narrowed down the strategic choices to three best fit strategies that appear complementary to the vision and goal of the company. An application of these three strategies were combined to develop the implementation program, intended to maximize AZAP?s strengths and opportunities.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, February 2010.